Volatile profile of fresh-cut ‘Rocha’ pear under various temperatures and oxygen levels - Gomes, M. H. (2019)
The objective of this work was to evaluate the effect of temperature and oxygen concentration on the volatile profile of packed fresh-cut 'Rocha' pear, to integrate flavor changes in the development of preservation technologies for fresh-cut fruit. Slices of 'Rocha' pear were packed in low-density polyethylene pouches, with varying fruit weight, film surface area and film thickness, and were stored at 0, 5, 10 and 15°C. After 5 days at 15°C, 8 days at 10°C and 10 days at 5 and 0°C, steady-state O2 and CO2 partial pressures were achieved and the volatile composition inside packages was measured. Samples were grouped in four classes depending on the levels of oxygen: high (>8 kPa), intermediary (8-1 kPa), low (1-0.5 kPa), and very low (<0.5 kPa, anaerobic metabolism). The acetate esters (methyl-, ethyl-, propyl-, butyl-, 2-methylbutyl-, pentyl- and hexyl-acetate) and alcohols (ethanol, butanol, 2-methyl butanol and hexanol) were analyzed for each atmosphere group. Volatile relative abundance was significantly affected by temperature and oxygen level. The levels of ethanol, the main alcohol detected, increased with temperature and oxygen depletion. Acetate esters represented 20 to 25% of the total volatiles, with butyl acetate accounting for almost 50% of the total acetate esters. Absolute levels of total acetate esters were significantly lower at 0°C than at higher temperatures, but 2-methylbutyl-, pentyl- and hexyl-acetate were significantly higher at this temperature. Decreasing oxygen levels to anaerobiose increased the total acetate esters, due to an increase in ethyl acetate, while other esters decreased. 2-Methylbutyl acetate, a flavor-important volatile in pear described as “fruity, banana, candy, citrus, peanut”, and hexyl acetate were more abundant at 0°C and oxygen levels above 8 kPa. These results suggest that the oxygen levels affect volatiles of fresh-cut pear; the design of modified atmosphere packaging should take this effect into consideration for shelf life termination.